(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The persistent failure of small scale businesses in Nigeria is alarming and needs timely intervention particularly in Enugu State. This, however, informed the present study to determine governmental and managerial factors hampering the growth of small scale enterprises in Enugu State. Two purpose statements, two research questions and four hypotheses guided the study. The research design was descriptive survey. Simple random technique was used to select 120 registered entrepreneurs for the study. The instrument for data collection was a structured questionnaire. The questionnaire was tested for validity and reliability. Using Cronbach’s alpha, the overall reliability coefficient was 0.82. Descriptive statistics of mean and standard deviation were used to answer the research questions. The t-test for non-correlated data was used to test the hypotheses at 0.05 level of significance. Findings from the study revealed among others that governmental and managerial factors hamper the growth of small scale enterprises in Enugu State. The findings revealed that the respondents differ significantly in their mean ratings on governmental and managerial factors that hamper the growth of SSEs based on location. Similarly, the findings revealed that the respondents do not differ significantly in their mean rating on governmental factor that hamper the growth of SSEs in Enugu State based on location. However, the respondents differed significantly in their mean rating on governmental factor that hamper the growth of SSEs based on years of experience. Similarly, the respondents do not differ significantly in their mean rating on managerial factor that hamper the growth of SSEs in Enugu State based on years of experience. Based on the findings, it was recommended among others that Enugu state should be consistent in her policies and regulations with regards to the affairs of small scale enterprises. Entrepreneurs in Enugu State should strive to employ competent managers to their enterprises as that will enhance enterprise growth and development among others.